The nexus among corporate board characteristics, governance practices and performance of state-owned enterprises in Ghana - Asiedu-Nketiah, Kwaku (Central University of Technology, 2023)
Purpose The primary aim of this study was to examine the nexus among corporate board characteristics, governance practices and performance of State-Owned Enterprises (SOEs) in Ghana. Methodology The research used a mixed-method approach. A literature review of related studies was done to identify the key board characteristics and good corporate governance practices of SOEs. Document analysis of the legal and regulatory framework governing SOEs in Ghana was also done and then followed by a quantitative approach to gather data from thirty-six (36) SOEs through stratified and simple random sampling and applied PLS-SEM to examine the intricate relationships between corporate board characteristics, governance practices, and the economic performance of SOEs. Key metrics like Return on Assets (ROA) and Return on Equity (ROE) were used to measure economic performance. Key findings Board size, board composition, board gender diversity, board age diversity, board members’ level of education and diversity in business/management expertise were identified as the key board characteristics from the literature review. For good corporate governance practices, the review of the literature showed board accountability, board independence, board fairness, board risk management and board transparency as the key corporate governance practices. Despite the robustness of the legal framework governing SOEs in Ghana, concerns arise regarding the potential influence of the executive branch, especially in board appointments. From the SEM analyses, neither the demographic nor cognitive characteristics of SOE boards have a significant direct or indirect influence on the economic performance of SOEs. Board size, middle-aged board members and elderly board members have a significant impact on board independence. Board size and middle-aged board members have a significant impact on board fairness, and the proportion of female board members has a significant impact on board transparency. The corporate governance practices, just like the board characteristics, do not have a significant direct impact on the economic performance of SOEs in Ghana. Research limitations Several potential limitations were identified in this study. The scope was confined to SOEs within Ghana, which could limit its generalisability to other contexts. The study's focus on only selected corporate governance practices might leave out other relevant practices influencing SOE performance. Additionally, the external economic, political, and social factors impacting SOE performance were not delved into, potentially missing out on providing comprehensive insights. Originality The empirical analysis within the thesis indicates that corporate governance practices, while theoretically pivotal, do not demonstrate a significant direct impact on the economic performance of Ghanaian state-owned enterprises. Furthermore, the anticipated mediating effect of these governance practices on the relationship between corporate board characteristics and SOE economic performance was not substantiated, suggesting a need to reassess the mechanisms through which governance structures influence financial success in this context.
Doctor of Philosophy in Management Sciences (Business Management)
Keywords: corporate governance practices; board characteristics; SOEs performance; legal frameworks.